IBU DAN PEMAKNAAN: KAJIAN SEMANTIK TERHADAP PUISI KARYA ANAK ABINAYA GHINA JAMELA - farninda Ninda Ninda (Raheema, 2020)
This paper describes the meaning of children's poetry by Abinaya Ghina Jamela. The intended meaning is lexical meaning, referential meaning, grammatical meaning, and classical meaning. This poem is sourced from the book Sehimpun Poetry Recipe for Making Jagat Raya. The poem chosen to be analyzed is the poem in which there is a Mother or Mother diction. Your poetry is taken to show your role in the process of writing children's poetry. The chosen poem is When I read a book. The method used is descriptive with Content Analysis and Library Study techniques. The results of the analysis note that the mother in the poem is interpreted as a person who is Merciful, Attention, Calm, Understanding, Helper, Hero, Smart, Clever to Explain Something, Good Listener, Joyful and Joyful, Smart Cooking, Skilled, Sources of Science, Inspirational, Special, Good Friends, Democracy (not curbing and giving trust), and Mother who also likes to nag. Based on the study of Semantic meaning in poetry when I read the book, there are more types of words used are nouns, namely 23 words, 16 verbs, and 2 adjectives, and the use of particle words totaling 6 words, 5 pronouns and 1 onomatopoeia and there are 19 lexical meanings, 18 referential meanings, 6 grammatical meanings, and 3 words meaning kias. Overall, the poem entitled When I Read a Book means the importance of reading books and inspiring figures of mothers for children. This paper can be used as consideration for parents providing guidance on writing poetry and literacy in the family environment. Keywords: Meaning, Poetry, Mother, and Child